Social technologies for online learning: theoretical and contextual issues. (2nd January 2016) - Kear, Karen; Jones, Allan; Holden, Georgina; Curcher, Mark
Abstract: Three exemplars are presented of social technologies deployed in educational contexts: wikis; a photo-sharing environment; and a social bookmarking tool. Students were found to engage with the technologies selectively, sometimes rejecting them, in the light of their prior conceptions of education. Some students (a minority in all the studies) were unsympathetic to the educational philosophy underpinning the technology's adoption. The paper demonstrates, through an examination of in-context use, the importance of sociocultural factors in relation to education, and the non-deterministic nature of educational technology. The academic study of technology has increasingly called into question the deterministic views which are so pervasive in popular discourse and among policy-makers. Instead, sociocultural factors play a crucial role in shaping and defining technology and educational technology is no exception, as the examples in the paper show. The paper concludes by drawing out some implications of the examples for the use of social technologies in education.